9. SOME CLINICAL CHARACTERISTICS AND DEPRESSIVE DISORDERS IN MYASTHENIA GRAVIS PATIENTS AT MILITARY HOSPITAL 103 (Tạp chí Y học Cộng đồng, 2025)
Objective: To investigate the clinical characteristics and depressive disorders in patients with myasthenia gravis.Subjects and Methods: A cross-sectional descriptive study was conducted on 83 myasthenia gravis patients treated at the 103 Military Hospital from July 2024 to March 2025.Results: Most patients had an education level ranging from primary to secondary school (61.45%), and manual laborers accounted for a high proportion (57.83%). The mean age of disease onset was 45.2 years, with later onset in males compared to females. The average disease duration was 8.2 years, with 69.88% having the disease for over 4 years. The prevalence of depressive disorders was 45.78%, predominantly moderate in severity (68.42%). There was no significant association between depression and education level, occupation, or age of onset (p > 0.05). Depression severity increased with disease duration, with the highest prevalence in patients with disease duration over 4 years (p < 0.05).Conclusion: Depressive disorders are common in patients with myasthenia gravis, with a positive correlation between disease duration and depression severity. Occupation, education level, and age of onset showed no clear impact on depression.
Keywords: Myasthenia gravis; depressive disorder; 103 Military Hospital